Lactobacillus Biofilms Influence Anti-Candida Activity - Parolin, Carola; Croatti, Vanessa; Laghi, Luca; Giordani, Barbara; Tondi, Maria Rosaria; De Gregorio, Priscilla Romina; Foschi, Claudio; Vitali, Beatrice (Frontiers in Microbiology, 2021)
Lactobacilli are the dominant members of the healthy human vaginal microbiota and represent the first defense line from pathogen infection, including vulvovaginal candidiasis. Biofilm is the predominant microbial growth form in nature, and the formation of biofilms inside the human body has important implications in health and disease. In particular, the formation of biofilm by members of the human resident microbiota is desirable, as it can improve microbial persistence and influence functionality. In the present study, we investigated the capability of 16 vaginal Lactobacillus strains (belonging to Lactobacillus crispatus, Lactobacillus gasseri, Lactobacillus vaginalis, and Lactobacillus plantarum species) to form biofilms, and we correlated their mode of growth to anti-Candida activity. L. plantarum strains were the best biofilm producers, and high variability was registered in the level of biofilm formation among L. crispatus and L. gasseri strains. Culture supernatants derived from Lactobacillus biofilm and planktonic growth were tested toward a panel of Candida clinical isolates (Candida albicans, Candida glabrata, Candida lusitaniae, Candida tropicalis, Candida krusei, and Candida parapsilosis) and their metabolome assessed by 1H-NMR. L. crispatus and L. plantarum strains exhibited the best fungistatic profile, and biofilms enhanced their anti-Candida activity; on the contrary, L. gasseri strains were more effective when grown in a planktonic mode. Biofilm/planktonic mode of growth also affects Lactobacillus metabolism, mainly influencing nitrogen and amino acid pathways, and anti-Candida activity is instead strictly related to carbohydrate metabolism. The present study underlined the strict interdependence between microbial mode of growth, metabolism, and functional properties. Biofilm formation by members of the healthy human microbiota represents a crucial issue in the field of microbial physiology and host–microbiota interactions, beyond supporting the development of new antimycotic strategies based on probiotics grown in adherence.